Tumoral chromoblastomycosis: a rare manifestation with typical complementary exams - John Verrinder Veasey; Beatriz de Abreu Ribeiro Machado; Rute Facchini Lellis; Laura Hitomi Muramatu; Clarisse Zaitz (Sociedade Brasileira de Dermatologia, 2015)
Abstract: Chromoblastomycosis is a chronic subcutaneous fungal infection caused by traumatic implantation of dematiaceous fungi in the skin. The clinical presentation is usually a verrucous plaque lesion and the diagnosis is confirmed by the visualization of muriform bodies at direct examination or at the histologic study. This report describes a rare case of tumoral chromoblastomycosis confirmed by histologic study and whose agent was identified by culture and micromorphology.